Identifying women who may benefit from higher dose omega-3 supplementation during pregnancy to reduce their risk of prematurity: exploratory analyses from the ORIP trial - Lisa N Yelland; Fang Huang; Maria Makrides; Karen P Best; Thomas R Sullivan; Robert A Gibson; Lucy A Simmonds; Sagar K Thakkar; Surabhi Devaraj; Irma Silva Zolezzi (BMJ Open)
Objectives The risk factors for prematurity are multifactorial and include low omega-3 status. Omega-3 supplementation in pregnancy has been found to reduce prematurity risk, particularly among women with low omega-3 levels. This study aimed to identify maternal characteristics that predict whether women with a singleton pregnancy will benefit from omega-3 supplementation to reduce their risk of prematurity.Design Exploratory analyses of a multicentre, double-blind randomised trial.Setting 6 tertiary care centres in four states in Australia.Participants 5328 singleton pregnancies in 5305 women recruited before 20 weeks of gestation.Interventions Fish oil capsules containing 900 mg omega-3 long-chain polyunsaturated fatty acids per day versus vegetable oil capsules consumed from enrolment until 34 weeks’ gestation.Outcome measures Early preterm birth (EPTB, <34 weeks’ gestation) and preterm birth (PTB, <37 weeks’ gestation) analysed using logistic regression models with interactions between treatment group and a range of maternal biological, clinical and demographic characteristics.Results Omega-3 supplementation reduced the odds of EPTB for women with low total omega-3 status in early pregnancy (OR=0.30, 95% CI 0.10–0.93). No additional maternal characteristics influenced whether omega-3 supplementation reduced the odds of EPTB. For PTB, women were more likely to benefit from omega-3 supplementation if they were multiparous (OR=0.65, 95% CI 0.49–0.87) or avoided alcohol in the lead up to pregnancy (OR=0.62, 95% CI 0.45–0.86).Conclusions Our results support previous findings that women with low total omega-3 levels in early pregnancy are most likely to benefit from taking omega-3 supplements to reduce their risk of EPTB. Understanding how other maternal characteristics influence the effectiveness of omega-3 supplementation on reducing PTB requires further investigation.Trial registration number ACTRN12613001142729.